2017
DOI: 10.6018/turismo.40.309741
|View full text |Cite
|
Sign up to set email alerts
|

El impacto cultural y social de los eventos celebrados en destinos turísticos. La percepción desde el punto de vista de los organizadores

Abstract: RESUMENEl objetivo de este estudio es analizar la existencia de asociación entre los impactos socioculturales generados por los eventos celebrados en localidades turísticas de Cataluña y la vocación turística de los mismos. Para ello los eventos analizados son clasificados en dos tipologías en función de si plantean objetivos turísticos en su misión y de si su programación contiene elementos adaptados a los gustos de los turistas. Los datos necesarios fueron recogidos por medio de una encuesta en línea realiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
0
12
0
2
Order By: Relevance
“…(3) strengthening the sense of well-being in the local community during the celebration of events. Furthermore, they highlighted that those events serve as a catalyst for the social and cultural values of the local community and are a means of showcasing them (González Reverté and Morales Pérez, 2017).…”
Section: The Theory Of Social Exchange (Set) and The Vice Model Application On Programmed Cultural Eventsmentioning
confidence: 99%
See 3 more Smart Citations
“…(3) strengthening the sense of well-being in the local community during the celebration of events. Furthermore, they highlighted that those events serve as a catalyst for the social and cultural values of the local community and are a means of showcasing them (González Reverté and Morales Pérez, 2017).…”
Section: The Theory Of Social Exchange (Set) and The Vice Model Application On Programmed Cultural Eventsmentioning
confidence: 99%
“…In an attempt to fill the gaps identified above, the study is based on a model developed around the core concepts of SET (Figure 1) The considered proposal suggests that impacts of programmed events are influenced by social exchange among community, industry and visitors, which has different social, economic and environmental impacts. The model further proposes that the impacts have to be considered according to the different moments of the social exchange: (i) initial moment of the exchange (Getz, 2008;González Reverté and Morales Pérez, 2017); (ii) exchange formation (Rollins and Delamere, 2007;O'Sullivan and Jackson, 2002;Van Niekerk and Coetzee, 2013;Bagiran and Kurgun, 2013;Chirieleison and Scrucca, 2017;Liu et al, 2018); (iii) post-interchange and the emergence of a health crisis (Gössling et al, 2020;Kachanoff et al, 2020;Nepal, 2020;Rowen, 2020).…”
Section: The Theory Of Social Exchange (Set) and The Vice Model Application On Programmed Cultural Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors found these trends in the growing demographic profile of those interested in sport activities, increasing the interest in a healthy lifestyle in the western world, increasing the demand for actively spent holiday time, increasing the interest in sport events related to restoration of local infrastructure and supporting the development of other travel services. The impacts on the local community can be seen in the social and cultural effects (Reverté and Pérez, 2018). Sport can also be used as an enhancement factor in the image of destination.…”
Section: Running Races and Sport Tourismmentioning
confidence: 99%